2013
DOI: 10.1002/ejic.201301033
|View full text |Cite
|
Sign up to set email alerts
|

A Contribution to the Direct Observation of Transient Phosphanylidene Complexes [RP=W(CO)5] (R: Me, Ph): A Revisited Approach to Their Electronic Structure by UV‐Photoelectron Spectroscopy

Abstract: An original approach involving a coupling in the gas phase between flash vacuum thermolysis (FVT) and UV-photoelectron spectroscopy (UV-PES) allowed the transient terminal electrophilic phosphanylidene complex [MeP=W(CO) 5 ] to be characterized; this is the first direct observation of this P-Me derivative. This approach also permitted the electronic structure of [PhP=W(CO) 5 ] to be revisited and confirmed the results obtained with the methylated analogues. In contrast, [p-NC-C 6 H 4 P=W(CO) 5 ] proved to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Our team has a homemade UV photoelectron spectrophotometer, which is constantly evolving to push the boundaries of analysis and detection. For instance, this technique has allowed us to recently identify the long‐sought transient terminal electrophilic phosphinidene complexes [RP=W(CO) 5 ], formed from the thermolysis of the corresponding 7‐phosphanorbornadiene complex after the loss of dimethyl 4,5‐dimethylphthalate at 160 °C . We have experimentally determined a full electronic cartography of these carbene analogous complexes through the determination of ionization potentials, real electronic “fingerprints”, which have been directly correlated with the molecular‐orbital energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…Our team has a homemade UV photoelectron spectrophotometer, which is constantly evolving to push the boundaries of analysis and detection. For instance, this technique has allowed us to recently identify the long‐sought transient terminal electrophilic phosphinidene complexes [RP=W(CO) 5 ], formed from the thermolysis of the corresponding 7‐phosphanorbornadiene complex after the loss of dimethyl 4,5‐dimethylphthalate at 160 °C . We have experimentally determined a full electronic cartography of these carbene analogous complexes through the determination of ionization potentials, real electronic “fingerprints”, which have been directly correlated with the molecular‐orbital energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…This generating method was first reported in 1985 by Mathey and coworkers. 39 45 It was reported that the energy barrier for generation of phenylphosphinidene pentacarbonyltungsten(0) is higher when generated from phosphiranes (27.5 kcal mol -1 ) than from 7-phosphanorbornadiene (23.5 kcal mol -1 chlorophosphinidene tungsten(0) complex. 36 The stereochemistry of this cycloaddition deserves special mention; the more hindered cis-isomer was formed almost exclusively, as compared to the non-separable mixture when the phenyl derivative was synthesized.…”
Section: Scheme 112 Electrophilic or Nucleophilic Modification Of Phmentioning
confidence: 99%